Attitudes of parents of children with communication disorders toward augmentative and alternative communication - Zlatić, Aleksandar; Arsenić, Ivana; Veljković, Zorica (Studies in Teaching and Education, 2025)
Parents' attitudes play a key role in the successful application of Augmentative and Alternative Communication (AAC) in children with communication disorders. The aim of the research was to examine parents' attitudes about AAC, including their awareness, readiness for implementation, barriers to using AAC, as well as emotional and social factors that influence the perception and use of AAC. 50 parents of children with communication disorders participated in the research. A specially constructed attitude scale was used. Analysis of the results showed that parents have a positive attitude towards AAC (M = 3.83, SD = 0.76). However, it was determined that the respondents have a moderate level of information and awareness about AAC methods, as well as that there is a need for additional education. Also, it was shown that lack of time for training and uncertainty about where to start with education were the most pronounced barriers to the implementation of AAC. Parents of girls had more positive attitudes towards AAC compared to parents of boys, while parents of children with autism perceived more barriers compared to parents of children with other diagnoses. Research results point to the need for additional parent education and better systemic support to facilitate the implementation of AAC. Further research should examine the influence of other factors on parents' attitudes and willingness to use AAC.
Keywords: augmentative and alternative communication, barriers, education, attitudes